Evaluating the infrared technique as a novel drying method of the turkish pastirma - S. G. Batman; O. Sipahioğlu; H. Yetim (Теория и практика переработки мяса, 2025)
Pastirma, a traditional dry-cured meat product from Turkey, is manufactured after a long drying process. In the study, we aimed to expedite the primary drying process, which is the lengthiest phase in pastirma production, by implementing the innovative infrared drying method, while preserving the sensory attributes of traditionally dried pastirma. Various physicochemical, microbiological and sensory characteristics of pastirma samples from two different muscles obtained by three various drying methods: traditional open-air (OA), climate-controlled chamber (CC) and infrared (IR) drying, were studied. The findings showed that IR drying, which reduced the drying time from 7 days to 2 days, produced the best quality in terms of sensory properties. Also, the lowest TBA values (0.07–0.13 mg/kg) were observed in IR dried samples. IR and CC drying solved the problem of uneven drying process of pastirma which was often encountered during the OA drying process. With the use of IR, the drying process of pastirma was rapid and the product quality was equivalent or even better than that of the other methods used in this research. This innovative approach of using IR drying can be adopted by the pastirma industry to facilitate the production of traditional products.